A Pressure-Bearing Microwave Transmission Line for Rapid Energy-Efficient Manufacturing Systems of High-End Composite Parts - Jing Zhou; Yingguang Li; Zexin Zhu; Xunyi Qi; Xiaozhong Hao (Chinese Journal of Mechanical Engineering)
Abstract Currently, a 2-port microwave transmission line with a glass window is usually used to transmit microwave energy to a pressure vessel while sealing the high-pressure gas. In this situation, the damage of the brittle glass window will inevitably result in disastrous accidents. In this paper, the idea of a “2+4”-port microwave transmission line is first proposed to solve this problem. A 4-port waveguide bridge structure is connected to the input port of a traditional 2-port structure, which can release the high-pressure gas safely when the glass window of the 2-port microwave transmitting structure fails. To test this idea, a “2+4”-port microwave transmission line at 2.45 GHz was designed and fabricated. The effectiveness of the whole system in microwave transmission was validated by both simulations and experiments. A high microwave transmittance of more than 97% in the simulation and 91% in the experiment was achieved. The long-time transmission of 15-kW microwave energy, 5 times higher than the previous work, was realized. Moreover, the effectiveness of the transmission line in releasing high-pressure gas (0.6 MPa) was validated by a series of fluid-structure interaction simulations. This research proposes a new transmission structure for transmitting microwave into a pressurized environment safely and efficiently, which can be promoted to a series of applications including vacuum electron devices, microwave ovens, and so on.